Multi-Stakeholder Innovation Based Quadruple Helix Thinking : Teenage Promiscuity Prevention in Indonesia - Saodah Susanti, Siti; Mustopa, Azizuddin (Institute of Education and Social Research, 2023)
The rising rates of teenage pregnancy and sexually transmitted infections demand a collaborative solution involving multiple stakeholders. To prevent promiscuity among teenagers, the Quadruple Helix Thinking approach is employed. The objective of this investigation is to examine the cooperation among stakeholders, notably Polsek, Puskesmas, and the Indonesian Ulema Council (MUI), in curbing promiscuity among teenagers residing around Pasir Jambu Village. This study employs a descriptive qualitative methodology to elucidate the role and efficacy of stakeholder collaboration in mitigating promiscuity among adolescents. The primary sources of data collection comprise input gathered from informants while the secondary data include supporting documents and records. The data gathering techniques involve surveys and interviews. The participants selected for this study consisted of junior and senior high school students from Jambu Village who were at risk for promiscuity. Interviews were conducted with both MUI and parents, following the specified criteria. Descriptive analysis was utilized, and the interactive model was adapted to analyze the data. The findings demonstrate that inter-agency collaboration effectively prevented promiscuity in Pasir Jambu Village